2014
DOI: 10.1515/jpem-2013-0455
|View full text |Cite
|
Sign up to set email alerts
|

How does autoimmune thyroiditis in children with type 1 diabetes mellitus influence glycemic control, lipid profile and thyroid volume?

Abstract: AIT accompanying DM1 is associated with worse glycemic control and lipid profile as well as a lower daily insulin requirement. The female gender is more likely to develop AIT and hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
2
9
0
2
Order By: Relevance
“…This is in agreement with previous studies that found no correlation between single and/or combined diabetes Ab positivity and diabetes control where some pancreatic function was preserved [39,40,46]. However, interestingly it was proved recently, that autoimmune thyroiditis accompanying T1DM is associated with worse glycemic control and lipid profile [47].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies that found no correlation between single and/or combined diabetes Ab positivity and diabetes control where some pancreatic function was preserved [39,40,46]. However, interestingly it was proved recently, that autoimmune thyroiditis accompanying T1DM is associated with worse glycemic control and lipid profile [47].…”
Section: Discussionsupporting
confidence: 93%
“…Polycystic ovary syndrome (PCOS) is the most common endocrine disease among women in reproductive age. It manifests mainly menstrual disorders and impaired fertility, clinical and biochemical hyperandrogenism, and characteristic polycystic image of ovaries in ultrasound scan [75]. Insulin resistance and elevated insulin PRACE POGLĄDOWE levels may be an important element in the pathogenesis of PCOS.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…The prevalence of metabolic syndrome in women with PCOS depends not only on genetic but also on behavioural factors. Weight loss by lowering insulin levels causes a decrease in androgen production and may lead to the return of ovulation [75]. On the other hand, the therapy with metformin appears to be effective in inducing ovulation and returning impaired fertility in PCOS.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
See 2 more Smart Citations